Now i am ready - Now i am not: The influence of pre-TMS oscillations and corticomuscular coherence on motor-evoked potentials - Schulz, Hannah; Uebelacker, Teresa; Keil, Julian; Müller, Nadia; Weisz, Nathan (Cerebral Cortex, 2014)
There is a growing body of research on the functional role of oscillatory brain activity. However, its relation to functional connectivity has remained largely obscure. In the sensorimotor system, movement-related changes emerge in the α (8-14 Hz) and β (15-30 Hz) range (event-related desynchronization, ERD, before and during movement; event-related synchronization, ERS, after movement offset). Some studies suggest that β-ERS may functionally inhibit new movements. According to the gating-by-inhibition framework (Jensen and Mazaheri 2010), we expected that the ERD would go along with increased corticomuscular coupling, and vice versa. By combining transcranial magnetic stimulation (TMS) and electroencephalography, we were directly able to test this hypothesis. In a reaction time task, single TMS pulses were delivered randomly during ERD/ERS to the motor cortex. The motor-evoked potential (MEP) was then related to the β and α frequencies and corticomuscular coherence. Results indicate that MEPs are smaller when preceded by high pre-TMS β-band power and low pre-TMS α-band corticomuscular coherence (and vice versa) in a network of motor-relevant areas comprising frontal, parietal, and motor cortices. This confirms that an increase in rhythms that putatively reflect functionally inhibited states goes along with weaker coupling of the respective brain regions. © 2013 The Author. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: corticomuscular coherence; ERD/ERS; gating by inhibition; motor network; TMS